(untitled) - Li, Chao-Jun (Hoboken, N.J., 2007)
Published almost a decade ago, the first edition has served as the guide for research in this burgeoning field. Due to the cost, safety, efficiency, and environmental friendliness of water as a solvent, there are many new applications in industry and academic laboratories. More than forty percent of this extensively updated second edition covers new reactions. For ease of reference, it is organized by functional groups. A core reference, Comprehensive Organic Reactions in Aqueous Media, Second Edition
Keywords: Chemistry, Organic,Solution (Chemistry),Hoá học, hữu cơ,Dung dịch (Hoá học)